PENGARUH PENYULUHAN KESEHATAN LINGKUNGAN TERHADAP TINGKAT PENGETAHUAN DAN PELAKSANAAN KESEHATAN LINGKUNGAN SMP NEGERI TAMBAKSARI KECAMATAN TAMBAKSARI KABUPATEN CIAMIS - Yoni Hermawan (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstrakHealthy behaviors at school showed unsatisfactory result, this can be seen from the result ofquick survey conducted in 2009 in the regency of Ciamis which shows: PHBS School levelI: 40,8%, PHBS School Level II: 33,3%, PHBS School Level 3: 20,5% and PHBS schoolLevel IV: 5,4%. From the result of the survey, behavioral problems are found: 83,7% studentssmoke, 63,6 students have not been exercising regularly, whereas environmental issuesinclude: Schools that haven’t owned latrines 63%, schools that haven’t managed theirwastes properly: 62%, and schools that haven’t had sewers:68%, the influence ofenvironmental health education to the level of students’ knowledge and implementation ofenvironmental health at one of the Junior High School at Tambaksari, CIamis District in2011. The research method is experimental method with pretest and post test approach. Theresult shows that before counseled, the student’s knowledge are largely categorized asadequate, that is 56 students (66,7%) and after they were given the counseling, the student’sknowledge largely categorized as decent, that is 51 students (60,7%). Based on the T-Testresult, the value of ñ is 0,000, so it can be concluded that there was influence of theenvironmental counseling on the level of knowledge in one of the Junior High School inTambaksari, CIamis District in the year of 2011 because the value of á is higher than ñ (á >ñ) (0,05 > 0,000). The implementation of environmental health before the counseling aregiven mostly are categorized as negative that is as many as 62 people (73,8%) and afterbeing given the counseling, student’s knowledge mostly categorized as positive that is 55people (65,5%). Based on the T-Test result, the value of ñ is 0,000, so it can be concludedthat there was influence of the environmental counseling on the level of knowledge in oneof the Junior High School in Tambaksari, CIamis District in the year of 2011 because thevalue of á is higher than ñ (á > ñ) (0,05 > 0,000), the result of the test results of the study ofthe influence of environmental health education on the level of students’ knowledge andimplementation of environmental health at one of the Junior High School in Tambaksari,CIamis District in the year 2011.